A Model for Developing Intercultural Competency of International Program Faculties - Opassatian, Kunlaya; Polsaram, Pansak; Kaemkate, Wanee (Dusit Thani College Journal, 2020)
The main purpose of this study was to construct a model for developing intercultural competency of international program faculties. The research procedure followed three steps: 1) to study current status of intercultural competency of international program faculties, The sample used in this study was 300 international faculties under Governmental Thai Higher Education and autonomous University. One instrument used was an intercultural competency of faculty in international program scale. Data analysis with Content Analysis, Descriptive Statistics were conducted by using the statistical software 2) to construct a model for developing intercultural competency of international program faculties by learning intercultural competency and guidelines for the development by analyzing and synthesizing concepts and the theories through relevant documents, research and international faculties by interviewing 20 faculties. One instrument used was an semi structure interview form “Conceptual of Intercultural Competency Development Model” 3) to evaluate the feasibility of the drafted model by 5 academic experts ; data were analyzed, using means and standard deviations. One instrument used were appropriateness and feasibility evaluation form. The research results were: 1) Status of intercultural competency of international program faculties had a high level of intercultural competency. In order of descending, attitude of multicultural 72.67%, communication and multicultural knowledge 67.67%, participation and teaching with multicultural student 63% . 2) A Model for Developing Intercultural Competency of International faculties was divided into 5 stages as follows: Phase 1 development before acting in international faculties consists of two methods: Seminar/ Training and International Exposure for international experience. Phase 2 development during acting in International faculties consists of three methods; Senior Coaching/ Mentoring/ Consulting, Intercultural Understanding Center and focus Group 3) The results of the assessment found that a Model for Developing Intercultural Competency of International program faculties were appropriateness and feasibility.as a whole was a high level.